Framing Gamification in Undergraduate Cybersecurity Education (Journal of The Colloquium for Information Systems Security Education, 2023)
Gamification presents potential benefits in courses that traditionally require the comprehension of complex concepts and a high level of technical and abstract thinking. Courses in Cyber Security Operations (CSO) undergraduate education meet these criterion. This research evaluates organizational constructs that have been applied to gamification applications (GAs) in CSO education. It utilizes framing theory and frame-reflective discourse analysis to outline frames based on engagement levels and analyzes the current distribution of GAs. The following organizational constructs for GAs in data structures and algorithms education apply to CSO education: Enhanced Examination (EE), Visualization of Abstract Ideas (VAI), Dynamic Gamification (DG), Social and Collaborative Engagement (SGE), and Collaborative Gamification Development (CGD). Three additional frames are identified: Missions and Quests (MQ), Simulations (Sim) and Aspirational Learning (AL). MQ GAs have process-driven quests, stories, and/or descriptive scenarios to augment engagement. Sim GAs use environmental immersion to demonstrate real world problem solving while allowing freedom of movement. AL GAs use goal-based designs like Capture The Flag (CTF) missions to enhance engagement. Twenty-seven existing CSO GAs fit within the MQ frame as CSO education lends itself well to these types of experiences. Seventeen CSO GAs fall within the AL GA frame, many of these manifesting as CTF missions. Seventeen CSO GAs fit in the EE Frame due to their optimization in the analysis of learning progress. Nine Sim GAs were successfully deployed in CSO education, followed by 4 VAI, 3 SGE, and 3 DG GAs.
Keywords: Cyber Security Education; Gamification; Framing Theory; Game-based learning; Pedagogy